Malaysian Apprenticeship Implementation: Issues and Challenges Towards Effective Employers Engagement - Kaprawi, Noraini; Rasi, Raja Zuraidah; Spöttl, Georg; Ismail, Affero; Razzaly, Wahid (Journal of Technical Education and Training, 2021)
While the jobs recovery is underway in many countries, persistently high rates of youth unemployment remain a significant labour market challenge. In response, there has been increasing interest in apprenticeships both as a route into employment and also in raising the skill levels of the workforce. Apprenticeship is one of the methods to promote young people's employment. It is historically prevalent and successful in Europe and is emulated in other countries around the world to promote employment especially amongst youth. Apprenticeships and other work-based training opportunities are valuable training pathways for improving the transition from school-to-work. At the local level, apprenticeship programmes can contribute to regional development objectives and provide local employers with the skilled workforce they require to remain competitive and create jobs. Therefore, this study was carried out to investigate the currents issues and challenges faced by Malaysian industrial employers in employer engagement of apprenticeship programmes through action research and descriptive studies. This action-based research as a methodology is to gather the responses of Malaysian local companies’ experiences in the manufacturing sector, across Multinational Companies (MNC), Government-Linked Corporations (GLC) and Small and Medium-scale Enterprises (SME) and identify the key issues and solutions that could create a beneficial prospect for TVET graduates and participating companies. Both descriptive quantitative and qualitative data from the survey questionnaires and interviews, respectively, were employed. 71 companies involved in the online survey and 6 manufacturing companies participated in the interviews and discussions as well as brainstorming. From the perspective of industries, this study found that the main key issues and challenges are: scarcity of competent industries instructors and coaches; provision of CPD; availability of apprenticeship bridging programs; teaching capacity; skills to deliver high quality employer focused apprenticeship; and industries and training providers collaboration. These six main issues are fundamentally systemic and highly intertwined in nature and will have to be resolved by all the stakeholders based on an agreeable working framework of apprenticeship in Malaysia. The findings of this study could provide policy makers and social partners with specific learnings to remove barriers to engaging employers in apprenticeship programmes, broaden access to training opportunities and improve the economic development and labour market performance of local areas.